Nonuniform estimate of maximum density convergence rate for independent random variables - Aksomaitis, A.; Jokimaitis, A. (Nonlinear Analysis: Modelling and Control, 1999)
The nonuniform estimate of convergence rate in the maximum density limit theorem of independent nonidentically distributed random variables is obtained. This result is generalization of the work presented in [1].